2010
DOI: 10.1002/mnfr.200900184
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and allergenicity assessment of enzymatically crosslinked β‐casein

Abstract: Crosslinking enzymes are frequently used in bioprocessing of dairy products. The aim of this study was to examine the effects of enzymatic crosslinking on IgE binding, allergenicity and digestion stability of beta-casein (CN). beta-CN was crosslinked by transglutaminase, tyrosinase, mushroom tyrosinase/caffeic acid and laccase/caffeic acid. The IgE binding to beta-CN was compared in vitro by CAP inhibition assay, ELISA inhibition as well as ex vivo by basophil activation assay. Crosslinked CNs were digested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…Various in vitro digestion models have been developed to assess the stability of food allergens during digestion, but systematic evaluation of the stability of food allergens that are active via the gastrointestinal tract have been currently tested in traditional pepsin digestibility models (Ladics, 2008;Thomas et al, 2004). In addition, more evidence is building up on the influence of food processing on pepsin digestion and allergenicity of proteins (Mills & Mackie, 2008;Monogioudi et al, 2011;Roth-Walter et al, 2008;Stanic et al, 2010). The effect of some phenolic compounds, resveratrol, catechin, epigallocatechin-3-gallate, quercetin and phenolics-rich beverages (red wine and green tea) on pepsin activity has previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…Various in vitro digestion models have been developed to assess the stability of food allergens during digestion, but systematic evaluation of the stability of food allergens that are active via the gastrointestinal tract have been currently tested in traditional pepsin digestibility models (Ladics, 2008;Thomas et al, 2004). In addition, more evidence is building up on the influence of food processing on pepsin digestion and allergenicity of proteins (Mills & Mackie, 2008;Monogioudi et al, 2011;Roth-Walter et al, 2008;Stanic et al, 2010). The effect of some phenolic compounds, resveratrol, catechin, epigallocatechin-3-gallate, quercetin and phenolics-rich beverages (red wine and green tea) on pepsin activity has previously been described.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Monogioudi et al (Monogioudi et al, 2011) -casein was cross-linked of by tyrosinase and demonstrated that enzymatically cross-linked b-casein was stable under acidic conditions and was more resistant to pepsin digestion when compared to non cross-linked b-casein. In the study of Stanic et al (Stanic et al, 2010) tyrosinase treated casein showed mitigated IgE binding reactivity, compared with the untreated CN, only in the presence of caffeic acid as mediator in BAT.…”
Section: Phenol Oxidases 431 Polyphenoloxidases (Tyrosinases)mentioning
confidence: 89%
“…Enzymatic processing of BLG decrease the bi-phasal pepsin-pancreatin digestibility of the monomeric and crosslinked protein, thus decreasing its nutritional value. Stanic et al (Stanic et al, 2010) crosslinked -casein (CN) by laccase and caffeic acid and demonstrated that crosslinking was not very efficient, leaving mostly monomeric CN modified by caffeic acid. Regardless to that ability of crosslinked CNs to activate basophils was significantly reduced in seven patients and reduced inhibition potential is possibly due to hindering of epitopes by monomer modification.…”
Section: Laccasesmentioning
confidence: 99%
“…One of the simplest models of protein digestion is the use of the purified major enzymes of stomach (pepsin) and pancreas (trypsin and chymotrypsin) (Horii et al 2009;Huang et al 2010;Kamata et al 1982;Nielsen et al 1988;Stanic et al 2010;Yagami et al 2000), implemented either separately of subsequently. The products of the digestion are usually analyzed using SDS-PAGE with the separation range from 3 to 20-30 kDa (Stanic et al 2010;Yu et al 2011) or reverse-phase HPLC (Bublin et al 2008).…”
Section: Isolated Enzymesmentioning
confidence: 99%
“…The products of the digestion are usually analyzed using SDS-PAGE with the separation range from 3 to 20-30 kDa (Stanic et al 2010;Yu et al 2011) or reverse-phase HPLC (Bublin et al 2008). In rare cases, mass spectrometry is also employed to characterize the digestion products (Dupont et al 2010).…”
Section: Isolated Enzymesmentioning
confidence: 99%